"What am I thinking? Is this normal?" A cross-sectional study investigating the nature of negative thoughts, parental self-efficacy and psychological distress in new fathers. (December 2019) - Wroe, Jaime; Campbell, Linda; Fletcher, Richard; McLoughland, Carmel
Highlights: Postnatal negative thoughts are typically experienced by fathers in the first year post-birth. Some degree of postnatal negative thoughts may be functional and representative of a healthy parenting transition. Many postnatal negative thoughts are not gender specific but instead shared, to varying degrees, by both parents. Negative thoughts that directly relate to parenting confidence and satisfaction may be representative of a dysfunctional transition to fatherhood. Abstract: Objective: The current study aimed to investigate an important aspect of mental health, negative thoughts, in new fathers during the postnatal year. The relationships between negative thoughts, parental self-efficacy and symptoms of depression were explored. Background: Positive and engaged father-infant relations provide a host of benefits for fathers, mothers, infants and the family system as a whole. However, there is little knowledge about the psychological factors influencing paternal engagement such as mental health and wellbeing. Methods: The study surveyed Australian fathers ( n = 300) recruited through social media. Well-established measures of depressive symptoms and parental self-efficacy were used, along with a researcher modified version of Hall and Wittkowski (2006) Postnatal Negative Thoughts Questionnaire (PNTQ) adapted for use in a paternal population. Results: Findings suggest negative thoughts are typical during the transition to fatherhood. To our knowledge, this is the first study that quantitatively explores and characterises paternal postnatal negative thoughts. Limitations: The sample was relatively homogenous with only a small sample of depressed participants. Data were from self-report instruments. Conclusions: While paternal postnatal negative thoughts are a normal and important functional part of a successful transition to fatherhood, a higher frequency of negative thoughts are linked to increased symptoms of depression and lower levels of perceived parental competence.